GIS-material for the archaeological project: Hearths beside stone fence at Lövsberg - Swedish National Heritage Board, UV Öst (Uppsala University, 2014)
The information in the abstract is translated from the archaeological report:
Due to the construction of a single-family house the Swedish National Heritage Board's contract archaeology division, UV Öst, performed a preliminary investigation in March 2005. The house will be built on a small plateau in a field, close by the archaeological site RAÄ 108 in Hogstad parish, a stone fence. Remains of hearths and pits, destroyed by ploughing, were discovered on part of the higher ground. UV Öst suggests that further archaeological measures are not needed, as long as the stone fence is not affected by the development.

Purpose:

The information in the purpose is translated from the archaeological report:
The purpose of the preliminary investigation was to conclude to what extent the stone fence RAÄ 108 would be affected by the planned development work. The aim was also to examine if there were any other archaeological remains close to the stone fence and, if so, to describe the type, extent and and, if possible, dating of the remains.

The ZIP file consist of GIS files and an Access database with information about the excavations, findings and other metadata about the archaeological survey.

Informationen i sammanfattning är hämtad ur rapporten för undersökningen:
Inför uppförandet av ett enbostadshus utförde Riksantikvarieämbetet UV Öst i mars 2005 en förundersökning. Arbetet är planerat att ske på ett flackt höjdläge i åkermark, i anslutning till fast fornlämning RAÄ 108, Hogstads socken, en stensträng. Inom en begränsad del av höjdläget hittades överplöjda härdrester och groprester. UV Öst bedömer att ytterligare arkeologisk åtgärd inte är nödvändig, förutsatt att den del av stensträngen som kvarligger i befintlig tomtgräns inte berörs vid de planerade markarbetena.

Syfte:

Informationen i syfte är hämtad ur rapporten för undersökningen:
Syftet med förundersökningen var att konstatera i vilken grad stensträngen RAÄ 108 berördes av de planerade arbetena. Målsättningen var också att utreda om ytterligare lämningar fanns i anslutning till stensträngen, konstatera dessas art och omfattning samt om möjligt datering.

ZIP-filen innehåller GIS-filer samt en Access datafil vilka innehåller information om schakt, fyndföremål, lämningstyper samt annan metadata om den arkeologiska undersökningen.
GIS-material för arkeologiskt projekt: Härdar intill stensträng vid Lövsberg
Keywords: historical period; historisk tid; prehistoric time; förhistorisk tid; HISTORY; HISTORIA; History and Archaeology; Historia och arkeologi; Archaeology; Arkeologi; Fieldwork archive; Fieldwork archive